Morphological and genetic characterisation of the root system architecture of selected barley recombinant chromosome substitution lines using an integrated phenotyping approach. (14th June 2018) - Canto, C. De La Fuente; Kalogiros, D.I.; Ptashnyk, M.; George, T.S.; Waugh, R.; Bengough, A.G.; Russell, J.; Dupuy, L.X.
Highlights: Model-based root phenotyping automates extraction of growth parameters. Combinatorial approaches for fast QTL mapping. Potential for accelerated identification of QTL for nutrient uptake efficiency. Abstract: Discoveries on the genetics of resource acquisition efficiency are limited by the ability to measure plant roots in sufficient number and with adequate genotypic variability. This paper presents a root phenotyping study that explores ways to combine live imaging and computer algorithms for model-based extraction of root growth parameters. The study is based on a subset of barley Recombinant Chromosome Substitution Lines (RCSLs) and a combinatorial approach was designed for fast identification of the regions of the genome that contribute the most to variations in root system architecture (RSA). Results showed there was a strong genotypic variation in root growth parameters within the set of genotypes studied. The chromosomal regions associated with primary root growth differed from the regions of the genome associated with changes in lateral root growth. The concepts presented here are discussed in the context of identifying root QTL and its potential to assist breeding for novel crops with improved root systems.